Optimasi Penerapan Teknologi Tepat Guna Mesin Peniris Bawang Untuk Meningkatkan Wirausaha Di SLB Purwosari Kudus - Zahro, Nafi' Inayati; Fiati, Rina; Kurniati, Diah (Universitas Islam Nahdlatul Ulama Jepara, 2023)
SLB Purwosari, Kudus district has levels for children with special needs with various disorders ranging from elementary school to high school. The special education curriculum for students with disabilities contains general programs, special programs and self-reliance programs which are developed to strengthen students with special needs for the provision of living economically independently, not depending on others. The problems faced by partners include (1) There are still many students with special needs who have completed their studies at SLB and have not been able to live independently, both independently in taking care of themselves and economically independent, (2) There is a need for additional variations / types of entrepreneurial skills which does not require a lot of thought and high concentration with minimal risk so that it can be followed by all students, (3) Inadequate infrastructure supporting entrepreneurial skills. The implementation method of this activity is the application of appropriate technology for onion chopper machines and cooking oil draining machines. Implementation of activities includes making tools, implementing tools, socializing activities by giving lectures on pre and post use of technological tools, procedures for making use of tools, mentoring, training and operating tools, as well as procedures for maintaining appropriate technology tools. The existence of this PKM activity has an impact on increasing knowledge and skills, as well as increasing the production of products produced by partners, namely students of SLB Purwosari Kudus.